1990
DOI: 10.1007/bf00026816
|View full text |Cite
|
Sign up to set email alerts
|

The forth estuary: a nursery and overwintering area for North Sea fishes

Abstract: The fish community of the Forth estuary, Scotland, has several components -estuarine resident species, diadromus migratory species, marine and freshwater adventitious species, marine juvenile migrants using the area as a nursery, and adults of marine species with seasonal migrations. The population changes during the period 1981-88 in six species representative of the last two categories are described here. The species are the juvenile gadoids, whiting, Merlangius merlangus (L.) and cod, Gadus morhua L., juven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(40 citation statements)
references
References 16 publications
(16 reference statements)
0
39
0
Order By: Relevance
“…The estuaries included here were sampled mainly by bed trawling or netting over the bed, methods which could underestimate the number of pelagic or planktivorous species (Elliott & Dewailly 1995). However, Elliott et al (1990) showed that bed trawling in shallow estuarine areas takes a representative pelagic population, at both qualitative and quantitative levels (Elliott & Dewailly 1995). Furthermore, as this study relied on a qualitative approach (species occurrence), some differences are expected when applying it to quantitative information (species abundances).…”
Section: The Guild Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The estuaries included here were sampled mainly by bed trawling or netting over the bed, methods which could underestimate the number of pelagic or planktivorous species (Elliott & Dewailly 1995). However, Elliott et al (1990) showed that bed trawling in shallow estuarine areas takes a representative pelagic population, at both qualitative and quantitative levels (Elliott & Dewailly 1995). Furthermore, as this study relied on a qualitative approach (species occurrence), some differences are expected when applying it to quantitative information (species abundances).…”
Section: The Guild Approachmentioning
confidence: 99%
“…Furthermore, as this study relied on a qualitative approach (species occurrence), some differences are expected when applying it to quantitative information (species abundances). For example, marine stragglers are typically represented by high numbers of species, but very low numbers of individuals (Elliott et al 1990), while planktivorous species may be highly represented owing to the large numbers of, e.g., clupeoids, which inhabit estuaries for part of the year (Elliott & Dewailly 1995).…”
Section: The Guild Approachmentioning
confidence: 99%
“…Estuaries have long been recognised as areas which naturally support high densities and production levels of fish, as permanent residents, during migration, or Naismith & Knights 1988, Elliott et al 1990 or which support fish species of international conservation value (e.g. Maitland 1974, Aprahamian 1988, anthropogenic pressures continue to threaten the integrity and quality of estuaries world-wide (McLusky 1989, GESAMP 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor which makes shallow coastal habitats favourable as a nursery area is the high productivity of benthos that can be utilized as food resource by both permanent and temporary inhabitants (Pihl & Rosenberg, 1982;Baden & Pihl, 1984;Jansson et al, 1985). This dependence on shallow bottoms in many juvenile marine species makes them vulnerable to several threats, including the loss of habitat and feeding areas (Elliott et al, 1990).…”
Section: Introductionmentioning
confidence: 99%